Comparison of luteal phase ovulation induction and ultra-short gonadotropin-releasing hormone agonist protocols in older patients undergoing in vitro fertilization. Issue 1 (1st January 2019) - Wang, Tianqi; Sun, Zhengao; Lim, June Ping; Yu, Yi
ABSTRACT: Many undergoing in vitro fertilization-embryo transfer (IVF-ET) procedures treatments have been tried for older infertile patients, but still can not reverse the aging effect on oocyte, and infertility treatment is expensive, even for people in developed countries. The study aimed to compare outcomes following the application of luteal phase ovulation induction (LPOI) and ultra-short gonadotropin-releasing hormone agonist (GnRH-a) protocols in patients aged more than 40 years undergoing IVF-ET and to examine the effectiveness and feasibility of LPOI. A total of 266 IVF-ET cycles in 155 patients aged 40 years and over were retrospectively analyzed. Of these patients, 105 underwent the ultra-short GnRH-a protocol (GnRH-a group) and 50 underwent LPOI (LPOI group). Various clinical outcomes were compared between these two groups using either t -tests or the chi-square test. The study showed patients in the LPOI group required a higher dosage of human menopausal gonadotropin and a lower dosage of recombinant follicle stimulating hormone than those in the GnRH-a group. Furthermore, though the total dosage of gonadotropin was higher in the LPOI, its cost was lower. Finally, fertilization rates were higher and high-quality embryo rates were lower in the LPOI group, and the live birth rate of LPOI group is higher than (GnRH-a group) . These between-group differences were all significant ( P < 0.05 ). Compared with the ultra-short GnRH-a protocol, LPOI may enable higher 2-pronuclear embryo fertilization rates and lower gonadotropin costs to be achieved, indicating that LPOI might be an ideal choice for older patients undergoing IVF-ET.